Electron density analysis of Bi0.95Ca0.05Fe1-xNbxO3(x = 0.02, 0.04, 0.06) samples that correlate microstructural, optical and magnetic properties - A. Sutha; M. Mohammed Sheik Sirajudeen; R. Rajesh; I. B. Shameem Banu (Discover Applied Sciences)
Abstract This article summarizes the electron density analysis of Bi0.95Ca0.05Fe1-xNbxO3(x = 0.02, 0.04, 0.06) samples that correlate the microstructural, optical, and magnetic properties prepared using the sol–gel method. The X-ray diffraction patterns of the synthesized samples reveal that the subtle peaks synchronize primarily with the R3c phase in these samples. The electron density and bonding characteristics of polycrystalline Bi0.95Ca0.05Fe1-xNbxO3(x = 0.02, 0.04, 0.06) samples were analysed using the Maximum Entropy Method. The two-dimensional contour map reveals that the covalent bonding distance between Bi/Ca-O and the ionic bonding distance between Fe/Nb–O converge well in the Bi0.95Ca0.05Fe0.96Nb0.04O3 sample and correlate with optical and magnetic properties. The bandgap energies of Bi0.95Ca0.05Fe1-xNbxO3(x = 0.02, 0.04, 0.06) are observed to be 1.78 eV, 1.97 eV and 1.72 eV respectively. The surface roughness shows an increasing trend in transmission spectra. As a result, the optical density and hence the refractive index reduce in all the samples. The maximum magnetization of Bi0.95Ca0.05Fe0.96Nb0.04O3 is considerably enhanced compared to other samples.